PMSM Wind Farm Aggregation Algorithm Based on Power Equivalence Principle - Shao, Haoshu; Cai, Xu; Yan, Heming; Zhou, Jiapei; Qin, Yao; Zhang, Zhixiang (Frontiers in Energy Research, 2021)
With the continuing increase of offshore wind farm power scale, it is urgent to propose a simplified wind farm model, which aggregates the entire wind farm into single or several aggregated wind turbine generators (WTGs), aiming to save computing resources and improve simulation speed. A novel aggregation algorithm that considers the power loss of offshore submarine cable is proposed, which is different from the traditional wind farm modeling method that adopts amplifying transformer as aggregation medium. Moreover, multi machine aggregation (MMA) algorithm is furtherly proposed to improve the aggregation accuracy. Simulation results verify that the proposed aggregation method can present the dynamic characteristics of wind farm with high accuracy, and can be popularized for other types of wind farm.